Convergence Theorems for Modified Inertial Viscosity Splitting Methods in Banach Spaces - Pan, Chanjuan; Wang, Yuanheng (Mathematics (Basel), 2019)
In this article, we study a modified viscosity splitting method combined with inertial extrapolation for accretive operators in Banach spaces and then establish a strong convergence theorem for such iterations under some suitable assumptions on the sequences of parameters. As an application, we extend our main results to solve the convex minimization problem. Moreover, the numerical experiments are presented to support the feasibility and efficiency of the proposed method.